The Effect of Cognitive and Affective Involvement on Intention to Use and Word of Mouth: The Case of Zoom Users In Indonesia - Nur Halimah Siahaan; Aldini Nofta Martini; M. Halim (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This study investigates affective and cognitive involvement that reflects psychological ownership and consumer-brand identification in the use of zoom application. Background Problems: The Zoom application was proposed because of its increasing popularity amid the Covid-19 pandemic. The selection of the zoom meeting application is the right way to find out how much the users want to continue this application both for themselves and to promote it to others by word of mouth (WOM). Novelty: This study examines the effect of cognitive and affective involvement on continuance intention to use and WOM by examining the mediating role of consumers’ psychological ownership and consumer-brand identification. Research Methods: 200 responses were analyzed using structural equation modeling (SEM) to test this study’s hypotheses. Finding/Results: The findings support the mediating role of the extent of consumer’s psychological ownership in describing the effect of affective involvement and continuance intention to use of a brand. In addition, the results support the mediating role of the extent of consumer-brand identification in describing the relationship between affective involvement and continuance intention to use a brand and engage in WOM promotion. Conclusion: These findings expand and unite existing theory on involvement and a continuing intention to use and engage in WOM.